Pengaruh Pengalaman Konsumsi dan Instagramable Place terhadap Minat Berkunjung Kembali Generasi Z pada Kafe Dimme di Kota Jambi - Uci Mardiana Tavonao; Husni Hasbulllah; Sylvia Kartika Wulan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to determine the effect of consumption experience and instagramable place on the repurchase intention of Generation Z at Dimme Cafe in Jambi City. The research approach used is quantitative, with the sampling method being nonprobability sampling. Data analysis technique used is multiple linear regression. The results of the study show that: 1) respondents' responses to the consumption experience variable are categorized as very high, instagramable place as high, and repurchase intention as very high; 2) the test results indicate that both consumption experience and instagramable place do not significantly affect the repurchase intention at Dimme Cafe in Jambi City, either partially or simultaneously. Based on the results of the study, it is recommended that cafe managers prioritize other factors that have a more significant impact, such as product quality, place comfort, service, and competitive prices. This research provides insights for cafe managers to consider other relevant factors in increasing customer repurchase intention, especially Generation Z.